1904
DOI: 10.1002/zaac.19040380121
|View full text |Cite
|
Sign up to set email alerts
|

Berichtigung

Abstract: B er i c h ti g u n g. Von A. QUTBIER und F. FLURY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1939
1939
1965
1965

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…10) in 1902 (170) showed that hydrazine spontaneously decomposed in contact with active Pt to liberate ammonia, nitrogen, and hydrogen. The equation proposed was Pt 2N2H4 -> 2NHS + N2 + H2 If hydroxyl ion was present, the proportion of hydrogen increased and the ratio of gases obtained approached the equation Pt 3N2H4-» 2NH3 + 2N2 + 3H2 -Two years later Gutbier and Neundlinger (77) showed that in the absence of the hydroxyl ion pure hydrazine in contact with oxygen-free platinum black decomposed to form 3N2H4 ^4NH3 + N2 Neither hydrogen nor nitrous oxide was formed.…”
Section: Catalytic Decompositionmentioning
confidence: 96%
“…10) in 1902 (170) showed that hydrazine spontaneously decomposed in contact with active Pt to liberate ammonia, nitrogen, and hydrogen. The equation proposed was Pt 2N2H4 -> 2NHS + N2 + H2 If hydroxyl ion was present, the proportion of hydrogen increased and the ratio of gases obtained approached the equation Pt 3N2H4-» 2NH3 + 2N2 + 3H2 -Two years later Gutbier and Neundlinger (77) showed that in the absence of the hydroxyl ion pure hydrazine in contact with oxygen-free platinum black decomposed to form 3N2H4 ^4NH3 + N2 Neither hydrogen nor nitrous oxide was formed.…”
Section: Catalytic Decompositionmentioning
confidence: 96%
“…The aminoguanidinium phosphotungstate (145), tetrabromoaurate (57), hexabromotellurite (56), and tetrachloropalladinate (55) have been described, and in addition a complex compound with thiourea (5) has been prepared. Hantzsch (58) has shown that a primary sulfate of aminoguanidine is formed in absolute sulfuric acid, aminoguanidine in this case acts as a tetraacid base.…”
mentioning
confidence: 99%